Implementasi Program Kebijakan Pelayanan Perumahan bagi Pegawai Negeri Sipil oleh Dinas Perumahan dan Kawasan Permukiman di Lingkungan Pemerintahan Kabupaten Mamberamo Tengah Propinsi Papua - Pasande, Agustinus Tridarsa; Muhlis Hafel; Yosephina Ohoiwutun (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to explore the factors that support and hinder the implementation of housing policies in Central Mamberamo, which factors are used as input for the Central Mamberamo Regency Government to take corrective steps and this study is also a mediator for Papuan civil servants to know for sure and comprehensively the benefits of livable houses for the safety and security of Papuan civil servants so that they are always healthy and enthusiastic in their activities and productivity. Data were processed using source triangulation techniques. The results of this study found that the implementation of the housing service policy program for civil servants by the Housing and Settlement Area Service of the Central Mamberamo Regional Government. From the aspects; a) Policy content; the policy of Law No. 1 / 2011 is then continued by making PKP, the contents of PKP 1) show that the Perkim Service has strong authority covering the determination of the allocation of official housing and the form of official housing. Context of Implementation. 1) housing program includes a) Staff, Barracks type 36. b) echelon 3 & 4 officials, Barracks type 42. c) echelon 2 officials, single house type 45. 2) Benefits of the policy, a) saving housing costs b) increasing PSN motivation in working. c) discipline. d) safety and e) security of civil servants. Factors that influence the housing service policy program for civil servants by the Housing and Settlement Area Service.  Keywords: Housing Services, Policy Programs, Settlements